Instilling Confidence in the Clinical Performance of Nursing Students - Wiratmo, Puji Astuti; Ramoo, Vimala; Nurachmah, Elly (International Journal Of Pedagogical Novelty (IJOPNOV), 2022)
There is existing concerns from clinical education that nursing students need to improve confidence on clinical performance. Confidence is basis of nursing education and determines graduates’ level of competence to enter workforce. Confidence promotes safe and effective patient care. However, it is challenging to understand concept of confidence and how nurse educators instill confidence with innovative teaching strategies. The purpose of this review is to discuss concept of confidence, factors influencing confidence, and teaching strategies to improve students’ confidence. Science Direct, EBSCOhost, and Pubmed databases were used to identify evidence based research related to students’ confidence and teaching strategies. The key words included confidence, nursing students, teaching strategies, and clinical performance. The articles were selected based on objectives, relevance, and year published. The result suggested that simulation should be modified by other strategies such as repeated simulation, team based learning, and self-debriefing. Another strategy is multidisciplinary teaching using technological tool such as video podcasting, immersive 3d interaction, game-based learning and video-based learning. Clinical confidence is an essential element in students’ clinical performance. Innovative and creative teaching strategies are needed to instill nursing student’s confidence. Further studies are needed in assimilation of teaching strategies for nurturing students’ clinical confidence.